2005
DOI: 10.1364/opex.13.004792
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive optics parallel spectral domain optical coherence tomography for imaging the living retina

Abstract: With the use of adaptive optics (AO), high-resolution microscopic imaging of living human retina in the single cell level has been achieved. In an adaptive optics confocal scanning laser ophthalmoscope (AOSLO) system, with a small field size (about 1 degree, 280 µm), the motion of the eye severely affects the stabilization of the real-time video images and results in significant distortions of the retina images. In this paper, Scale-Invariant Feature Transform (SIFT) is used to abstract stable point features f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
154
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(158 citation statements)
references
References 21 publications
4
154
0
Order By: Relevance
“…A simple 1-D FFT (after λ → k interpolation, k is wavenumber) along the spectral dimension of the data yields an X-Z cross-sectional image. [94][95][96][97][98][99] Zuluaga and Kortum were among the first to demonstrate a working LF FD OCT system using a technical sample. 94 Grajciar et al developed the first LF FD OCT system (shown in Fig.…”
Section: Line-field Octmentioning
confidence: 99%
“…A simple 1-D FFT (after λ → k interpolation, k is wavenumber) along the spectral dimension of the data yields an X-Z cross-sectional image. [94][95][96][97][98][99] Zuluaga and Kortum were among the first to demonstrate a working LF FD OCT system using a technical sample. 94 Grajciar et al developed the first LF FD OCT system (shown in Fig.…”
Section: Line-field Octmentioning
confidence: 99%
“…One of the most promising applications of AO systems in ophthalmology is optical coherence tomography (OCT) which provides depth resolution, allowing clinicians to visualize different retinal layers (Zhang et al 2005). Moreover, when incorporated into a scanning laser ophthalmoscope (SLO), AO systems have significantly improved the lateral resolution of this type of ophthalmoscopy (Zhang et al 2006).…”
Section: Modeling Of a Mfdm For Retinal Imaging 181mentioning
confidence: 99%
“…Both of these groups used adaptive optics technology with a Hartmann-Shack wavefront sensor and a deformable mirror operating in a closed loop. Miller et al [8] have recently described the use of AO line-illumination parallel Fourier Domain OCT allowing photoreceptor imagining on single B-scans. Improvements in transverse resolution sufficient to image the photoreceptor mosaic have also been realized with adaptive optics in flood-illumination imaging and the scanning laser ophthalmoscope [9][10], but axial resolution is lower than that expected from OCT.…”
Section: Introductionmentioning
confidence: 99%